Availability of Essential Macronutrients in Hiyung Chilli Growth Media Under a Floating Raft System - Syawalluna, Andini Putri; Saputra, Riza Adrianoor (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2026)
Hiyung chilli (Capsicum frutescens) is a local cultivar grown in the lowland swamp agroecosystem of Hiyung Village, South Kalimantan, where cultivation is constrained by seasonal flooding and water fluctuation, limiting planting to once annually. This study evaluates the availability of essential macronutrients, such as nitrogen (N), phosphorus (P), and potassium (K), in floating raft-based growing media supplemented with NPK fertilizer. A descriptive method was applied using three fertilizer doses: 0, 150, and 300 kg ha⁻¹. Results show that increasing fertilizer doses proportionally enhances nutrient availability, including NH₄⁺ (189,54 ppm), NO₃⁻ (26,17 ppm), available P₂O₅ (17,57 ppm), and K (0,65 me 100 g⁻¹), accompanied by a pH increase to 5.54. Correlation analysis reveals a strong to very strong positive relationship between pH elevation and macronutrient availability, and a weak to very strong relationship between nutrient levels and plant growth. These findings support sustainable nutrient management strategies to improve Hiyung chilli productivity under swamp-based cultivation conditions.